Realizing service migration in industry—lessons learned. Issue 6 (3rd May 2011) - Nasr, Khalid Adam; Gross, Hans‐Gerhard; van Deursen, Arie
Abstract: In this paper, we present two descriptive case studies covering the re‐engineering and further evolution of adopting service‐oriented architecture (SOA) in the industry. The first case was carried out for a company in the transport sector with an application portfolio of over 700 systems. The second case study was conducted for an organization in the public sector. The goal of both case studies is to identify the possible benefits and drawbacks of realizing SOA in large organizations in order to obtain a better perspective on the real, rather than the assumed, benefits of SOA in practice. We describe how the two cases were developed and carried out, and discuss the experiences gained and lessons learned from adopting SOA in the two organizations. Based on these findings, we propose several directions for further research. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : This paper presents two case studies that cover the re‐engineering and further evolution of adopting service‐oriented architecture (SOA) in the industry. The goal of both case studies is to identify the benefits and drawbacks of realizing SOA in large organizations. This is done to obtain a better perspective on the real, rather than the assumed, benefits of SOA in practice. Based on these findings and the lessons learned, directions for further research are proposed. Copyright © 2011 John Wiley & Sons, Ltd.